P93 Hiv testing in an integrated sexual health service. (18th May 2015) - Oduru, Mamatha; Hamill, Matthew; Pal, Nisha; Desmond, Noreen
Abstract : Background/introduction: National standards recommend eighty percent of new sexual health patients should have an HIV test. Thames Valley data from 2013 highlighted lower uptake of HIV testing in the region's only integrated sexual health service (SHS) compared to two local non-integrated services. Aim(s)/objectives: This audit measured differences in HIV testing uptake between genitourinary (GU) and contraception consultations in an integrated SHS and assessed the impact of a publicity campaign. Methods: SHHAPT codes and demographics were collected from all new patients over two weeks; non-coded patients were excluded. Retrospective case-note review differentiated GU from contraception presentations. 'National HIV testing week' posters were displayed in week 2. Data were analysed in Microsoft Excel. Results: Total sample size was 205 patients (week 1, N = 114, week 2, N = 91). 63% were female and 96% heterosexual. Age range was 14 to 83 (mean 31, standard deviation 13), with 36 countries of birth. Patients presented for GU issues (N = 126; 61%), contraception (N = 67; 33%) and combined (N = 12; 6%). HIV uptake differed between GU and contraception groups (81% v 30%). Between weeks 1 and 2, testing uptake increased by 4.5% in the total population and 10.6% in the GU group with minimal change in the contraception group. Discussion/conclusion: HIV testing uptake is higher in GU presentations compared to contraception presentations. This large discrepancy impacts overall testing figures. A publicity campaign may have increased GU uptake but had no impact on contraception consultations. Targeted education and opt out testing should be considered in integrated services.